Association of Vitamin K Insufficiency as Evaluated by Serum Undercarboxylated Osteocalcin With Frailty in Community-Dwelling Older Adults - Azuma, Kotaro; Osuka, Yosuke; Kojima, Narumi; Sasai, Hiroyuki; Kim, Hunkyung; Inoue, Satoshi (Frontiers in Aging, 2022)
Frailty is the state of having a reduced ability to recover from stress. Intervention in frailty is important for fulfilling healthy longevity. Vitamin K is a fat-soluble vitamin contained in vegetables and fermented foods. Although vitamin K is shown to be associated with several age-related diseases, studies on the association of vitamin K intake and frailty in the elderly population are limited. In the present study, a total of 800 community-dwelling older adults (mean age = 75.9) were recruited for a comprehensive geriatric health examination, including frailty evaluation based on the Japanese version of the Cardiovascular Health Study criteria. Serum concentrations of total osteocalcin (OC) and undercarboxylated osteocalcin (ucOC) were measured. The ratio of ucOC and OC (ucOC/OC), which reflects vitamin K insufficiency, was calculated for each participant, and the values were divided into quartiles. A binary logistic regression analysis was performed to evaluate the risk of frailty for each quartile of ucOC/OC, with the lowest quartile as the reference. Significant association of frailty and the highest quartile of ucOC/OC was found with the odds ratio of 2.49 (p = 0.023) with adjustment with age, sex, body mass index, dietary intake, and several clinical characteristics. When the analysis was repeated in each component of frailty, the highest quartiles of ucOC/OC had the tendency of association with “slow walking speed” and “low activity.” Our findings demonstrated the association between vitamin K insufficiency and frailty in the elderly population. Our analysis also suggests that vitamin K insufficiency could be associated with selected components of frailty.